Certain fermented dairy foods as a source of multibiotics and multimetabolites: a comprehensive review - Ağagündüz, Duygu; Ertaş Öztürk, Yasemin; Ayhan, Büşra; Bulmuş-Tüccar, Tuğçe; Özenir, Çiler; Erdoğan Gövez, Nazlıcan; Ozogul, Yesim; Esatbeyoglu, Tuba; Ozogul, Fatih (Frontiers in Nutrition, 2025)
Fermentation, a traditional biotechnological food bioprocessing, has been used for centuries. It enables the preservation of perishable foods and designing a novel food product with different taste and rheological properties. Fermented foods are defined as “foods made through desired microbial growth and enzymatic conversions of food components by The International Scientific Association of Probiotics and Prebiotics (ISAPP). Regarding this, the most popular fermented products are fermented dairy products which are commonly produced by lactic acid fermentation such as fermented milk, yogurt, kefir, sour cream, cultured buttermilk and cheeses, and some novel fermented dairy products. Accumulated literature suggests that fermented dairy products are one of the important sources of some nutritional biotics like probiotics, prebiotics, postbiotics and some bioactive metabolites. At the molecular level, the fermented dairy products’ matrices are composed of hundreds of compounds and various metabolites, including organic acids and derivatives, carbohydrates, lipids and lipidomics, milk fat globule membrane (MFGM), proteins, amino acids, bioactive peptides, nucleic acids, vitamins, minerals, and aroma volatiles, etc. which contribute to their technological and aroma properties. A number of preclinical and clinical studies suggest that these biotics and metabolites have promising health effects as well as their technological benefits. These effects of fermented dairy products significantly vary according to plenty of factors such as the milk types and composition, products’ microorganism profiles, matrix, added ingredients, etc. This comprehensive review focuses on the fermented dairy foods as a source of multibiotics and multimetabolites with technological importance and health-promoting effects on human health.